EVALUATION OF PLUS AND THE BEST OAK TREES BY THEIR 20 YEARS OLD PROGENIES GROWTH AND DEVELOPMENT - Los, S. A. (Forestry and Forest Melioration, 2018)
Introduction Despite the active use of molecular genetic, physiological and other modern techniques at forest tree improvement, determining of plus trees selection values is impossible without their progeny testing. Evaluation by progeny is realized by complex of features, in particular the classic approach provides the determination of height, diameter, condition and straightness of stems or breeding category. Additional indicators such as the branches angle, form of the crown, wood density and others are often used. The aim of this work was to develop methodological approaches of assessing the oak plus trees progeny and their approbation on the example of 20 years old progeny test in SE “Hutyanske Forest Economy”. Materials and Methods The progeny test in SE “Hutyanske FE” is created in the spring of 1996 in forest grown conditions D2. Progenies of 17 plus and the best trees of primary and secondary selection and a seed mixture from clonal seed orchards No 3, 3a and 4 of Pivdenne forest subdivision of Kharkiv Forest Research Station (candidate to varieties ’Danilovskiy’) are represented in the test. Seedlings from the combined seeds from the forest subdivision were planted as the control. The observation was carried out in 2014, when the plants biological age was 20 years old. During the observation, the survival, diameter, height, selection category, condition, presence of defects and damage by conventional tree improvement methods were determined for each of the tree. Additionally, growth forms were determined by three point scale. To evaluate the progeny stem quality in the test the scale based on the distribution of trees in variants by plant selection categories was used [10]. It is taken into consideration that the indicators which characterize the growth, condition and quality are expressed in different units and the scales consist of a different number of gradation, for final comprehensive assessment of the plus trees all indicators were brought to the unified system - 5-point evaluation by all indicators. Results Plant survival in variants ranged from 31.1 (L-3) to 60.8 (K-31). Among the 17 examined progenies, 11 are above the control by 11.4 % in diameter and 5 progenies exceed control by 13.5 % in height on average. 7 progenies exceed the control in diameter by 8.2 % in average and 12 progenies have exceeding in height - by 9.7 % in average. Only two progenies (C-22/26 and Tr-15/17) are significantly higher than the control in diameter (by 38.3 and 20.7 %, respectively), and two ones (D-3 and K-36) are significantly behind (by 13.7 and 14.8 %, respectively). Three progenies (D-5, C-22/26 and TS-15/17) are significantly higher than the control height (by 12.1-17.9 %). Four variants (K-38, P-20 and-13 May-2) are significantly behind in height (by 13.4-15.7 %). Progenies Tr-15/17 and C-22/26 are significantly higher than the control both by height and diameter. Variety ’Danylivskiy’ has the indices on the control level. The volume of average tree trunk is from 0.023 (D-3, K-36) to 0.63 (C-22/26). The best variant exceeds the control (0.034 m3) in 1.9 times. The share of trees of I and II selection categories in progenies ranged from 9.4 (Ta-13) to 46.5 % (Ta 3). Moreover, 10 progenies and the control were evaluated as high quality progenies and included into the 1st group of quality. 6 variants (K-31, 38, P-20, 21, Ta-13 and Tr-2) assessed as progenies with satisfactory quality stems (the 2nd group of quality). One variant only (K-36) was included into the 3rd progeny group with poor stem quality. Trees of good and excellent condition are quantitatively dominated in most variants. The share of trees of poor condition is from 6.2 % (P-21) to 31.7 % (D-3). Dry trees in small quantities were noted in two variants only, D-3, Ta-7. Condition index of variants ranged from 2.0 to 2.8 points. Complex evaluation by 6 growth and development indicators allowed distributing the variants on 4 groups. Correlations between the height of 2 years old variants and other indicators in following years were not found, while there are strong correlations between the heights of 5, 10 and 20 years old progenies (r = 0,71-0, 90), as well as by diameters in 10 and 20 years old progenies (r = 0,83). In all cases, correlations between the heights are higher. This indicates the ability to predict the growth intensity by diameter in 20 years according to observation in 5 and 10 years. Form of growth is strongly associated with the height and diameter. So, for the 10 years old progenies, the correlation with height is higher than with the diameter (r = -0.95 and -0.85, respectively), and for 20 years old ones it is opposite (r = -0.57 and -0.84, respectively). Conclusions A method of a complex summary assessment of plus trees by the growth and development of their progenies are proposed based on the total points of assessment by 6 indices, each of which in turn evaluated by 5-point scale. According to the comprehensive assessment the examined progenies of best and plus trees are divided into 4 groups: - Very promising (C-22/26) - Promising (Tr-15/17 B-5, B-42) - Relatively promising (D-3 K-33, K-35, K-38, P-20, P-21 Ta-3 Ta-7, Tr-2, variety ’Danilovsky’) - Unpromising (K-31, K-36, L-3, Ta-13). C-22/26 Tr-15/17, D-5, B-42 trees were proposed to consider as candidates for elite and used for clonal seed orchard of second level creation. Correlation analysis did not find any relationships between the height of 2 years old variants and other indices in the following years, while there are strong correlations between the heights of 5, 10 and 20 years old progenies (r = 0,71-0, 90), as well as by diameters in 10 and 20 years old progenies (r = 0,83). Form of growth strongly connected to the height and diameter. So, for the 10 years old progenies, the correlation with height is higher than with the diameter (r = -0.95 and -0.85, respectively), and for 20 years old ones it is opposite (r = -0.57 and -0.84, respectively). Trees with strong stem and clearly defined central shoot upward have greater diameter and height indices more often.